Formulasi Dan eval_uasi Sediaan Handbody Lotion Ekstrak Pegagan (Centella Asiatica L.) Kombinasi Niacinimade - M. Ali, Nur Faizah (Jurnal Penelitian Farmasi Dan Herbal, 2025)
Pegagan extract comes from the pegagan plant (Centela Asiatica L.) containing saponins, asiticosides, asiatic acid, and madecasate which can stimulate the production of collagen I, a protein that stimulates the wound healing process. This plant can be used as a raw material for skin care. Pegagan in the form of hand body lotion is used for skin care and other body parts. This study aims to determine the effect of differences in the concentration of Stearic Acid and cetyl alcohol in the Handbody Lotion formulation on the results of the preparation eval_uation test. Physical eval_uation tests of the preparation include organoleptic tests, homogeneity tests, pH tests, viscosity tests, and stability tests. The test results obtained the optimum formula, namely formula 1 with a ratio of cetyl alcohol and stearic acid with a desirability value of 1. The results of the stability test showed that the handbody lotion preparation was stable from the organoleptic parameters, homogeneity, pH, viscosity